Analysis of Barriers to Electronic Medical Record Implementation at Tasikmadu Health Center: Study Based on 5M Aspects - Widiantoro, Reza; Harjanti; Kartika Dewi Mayasari; Isnaini Dewi Anjani (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
Peraturan Menteri Kesehatan nomor 24 Tahun 2022 concerning Medical Records through the policy states that Health Service Facilities are required to implement an electronic patient medical history recording system. The transition process will be carried out no later than December 31, 2023. This research method uses qualitative descriptive. The research subjects are health center officers. Instruments and data processing are Interviews and Observations. To identify the causes of the problems, they are grouped into 5M (man, materials, methods, money, machines). The results of the study from the 5 aspects used to identify problems at the Tasikmadu Health Center, found several obstacles in the implementation of manual medical records to electronic medical records based on the man factor, namely, not all medical record officers have a medical record background, training is still needed for doctors, midwives, nurses. Materials factor, namely the need to procure new Hardware. Method factor, there is no SOP for the use of RME for each section at the Health Center. Money and machine factors, which are obstacles that often occur in the maintenance process of the system, due to the absence of IT employees. Based on these problems, there are several strategies that can be used to solve these problems, such as adding IT officers; providing training to doctors, midwives, and nurses who use RME; performing maintenance and updating the network; updating computers with the latest specifications; and creating (SOP) for implementing RME for each section.